Exchange Rate as a Determinant of Corporate Loan Defaults in a Euroized Economy: Evidence from Micro-Level Data. Issue 3 (3rd May 2016) - Atanasijević, Jasna; Božović, Miloš
Abstract : This article examines the factors that induce nonperformance of loans in an economy with a high degree of currency substitution. Using a well-diversified portfolio of corporate loans from a Serbian bank between 2008 and 2012, we find three key determinants of loan default: exchange rate, lagged GDP growth rate, and loan size. Exchange rate depreciation is associated with an increase in the default rate whether the loan is denominated in foreign or local currency. By controlling for positive effects on revenue, we show that this finding can be attributed to an increase in the firms' net input costs due to the depreciation.